Physical autocatalysis driven by a bond-forming thiol-ene reaction. - Bissette, A; Odell, B; Fletcher, S (Nature Publishing Group, 2014)
Autocatalysis has been extensively studied because it is central to the propagation of living systems. Chemical systems which self-reproduce like living cells would offer insight into principles underlying biology and its emergence from inanimate matter. Protocellular models feature a surfactant boundary, providing compartmentalization in the form of a micelle or vesicle and any model of the emergence of cellular life must account for the appearance, and evolution of, such boundaries. Here, we describe an autocatalytic system where two relatively simple components combine to form a more complex product. The reaction products aggregate into micelles that catalyse molecular self-reproduction. Study of the reaction kinetics and aggregation behaviour suggests a mechanism involving micelle-mediated physical autocatalysis and led to the rational design of a second-generation system. These reactions are driven by irreversible bond formation and provide a working model for the autocatalytic formation of protocells from the coupling of two simple molecular components.